2021
DOI: 10.3390/antiox10081320
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Improves the Redox Homeostasis to Alleviate Glyphosate Toxicity in Tomato Plants—Are Nanomaterials Relevant?

Abstract: Given the widespread use of glyphosate (GLY), this agrochemical is becoming a source of contamination in agricultural soils, affecting non-target plants. Therefore, sustainable strategies to increase crop tolerance to GLY are needed. From this perspective and recalling silicon (Si)’s role in alleviating different abiotic stresses, the main goal of this study was to assess if the foliar application of Si, either as bulk or nano forms, is capable of enhancing Solanum lycopersicum L. tolerance to GLY (10 mg kg−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 90 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…Notably that the three isoforms are inhibited by 50x in the Early-log and stationary phases, such as SOD. A generalized inhibition of the antioxidant enzymes was found in tomato plants, for instance, suggesting the occurrence of great redox disturbances by glyphosate ( Soares et al., 2021 ).
Figure 6 CAT gel activity in 0x, 1x, 10x, 40x, and 50x treatments, in the early-log and mid-log growing phases of P. fluorescens CMA-55.
…”
Section: Resultsmentioning
confidence: 99%
“…Notably that the three isoforms are inhibited by 50x in the Early-log and stationary phases, such as SOD. A generalized inhibition of the antioxidant enzymes was found in tomato plants, for instance, suggesting the occurrence of great redox disturbances by glyphosate ( Soares et al., 2021 ).
Figure 6 CAT gel activity in 0x, 1x, 10x, 40x, and 50x treatments, in the early-log and mid-log growing phases of P. fluorescens CMA-55.
…”
Section: Resultsmentioning
confidence: 99%
“…Seeds sample was incubating in 3 ml of a reaction mixture [10 mM sodium phosphate buffer (pH 7.8), 10 mM sodium azide (NaN 3 ), and 0.05% (m/v) nitroblue-tetrazolium (NBT)]. Finally, H 2 O 2 level was measured based on supernatant absorbance value (OD) at 390 nm with the method of Hasanuzzaman et al (2021) , and O 2 ⋅ – level was calculated based on the absorbance of the supernatant at 580 nm according to the method of Soares et al (2021) . All the samples were assayed with four biological replicates.…”
Section: Methodsmentioning
confidence: 99%
“…Antioxidant enzymes analysis was performed based on the method of Soares et al (2021) . Potassium phosphate buffer (pH 7.5) was utilized for seeds homogenization.…”
Section: Methodsmentioning
confidence: 99%
“…Once accumulated inside plant tissues, xenobiotics can interact with several cellular players such as proteins and nucleic acids, inducing a cascade of downstream effects which usually involve the disruption of redox homeostasis [ 155 , 165 ]. For instance, Gomes et al [ 166 ] and Soares et al [ 167 , 168 ], when reporting the biochemical and cellular effects of glyphosate (GLY) exposure on willow ( Salix miyabeana Seemen) and tomato ( Solanum lycopersicum L.) plants, revealed that the plants underwent a state of oxidative stress, measured by the increase in LP and the overaccumulation of ROS, while also experiencing changes to the antioxidant system, including an increase in proline levels. The upregulation of proline production has also been reported in response to pharmaceuticals [ 158 ], although proline metabolism seems to fall into a species-specific regulation in response to these organic pollutants.…”
Section: The Involvement Of Proline In Plants Facing Issues Of Soil D...mentioning
confidence: 99%